Correlating dry wear turning and pin‑on‑disc tests: a cost‑effective approach to machinability evaluation for low carbon steel grades - Martínez Krahmer, Daniel Osvaldo (2023)
Machinability tests play a crucial role in the metalworking industry despite their inherent cost and time requirements. This study aims to introduce a novel approach by establishing a correlation between the dry wear turning and pin-on-disc tests, potentially enabling their interchangeability. The industry is particularly interested in this challenge due to the simplifed implementation and reduced costs and time compared to the conventional turning test. The correlation between the dry wear turning and pin-on-disc tests was investigated using three low carbon steel grades (12L14, 1212, and 1018) and three medium cutting speeds (150, 180, and 240 m/min). Additionally, a comprehensive cost-energy comparison is conducted to underscore the signifcance of identifying a laboratory test equivalent to the traditional machinability test. The obtained results reveal a strong correlation between both wear tests. Furthermore, the relative cost analysis demonstrates that the pin-on-disc test costs only 14% of the long-duration turning test, emphasizing its cost-efectiveness.